اللغة في شعر عمرو بن أحمر الباهلي - الموسوي، فضيلة سالم إسماعيل; غالب، علي ناصر (الحلة, 2015)
The theme of the research is to: Language in hair Amr ibn red Baahili, which represents the study of language in the ancient Arab poetry curriculum descriptive moderately important factor in the collection of properties Tnmaz by language in poetry from other uses other language, and we infer by knowing the nature characterize the poet to Doath on identify obvious features of templates drafting and installation, built organized poetry, music and his words, and understand the ingredients included Qrihth of meanings, and therefore knowledge of contexts procedural and investment poetic possibilities of language available, this study was an analysis of the language levels of the four in the poetry of Ibn browned. Presented at the first search prelude includes a definition of the poet and his place among linguists and grammarians, and the impact of an environmental to the consolidation of certain linguistic features, and dealt with in the first chapter study of the level of the voice and the statement of the effect of the rhythm of the vote, and Kiffa balancing Alasaha internal voices and compositions and rhythm of the part of the poetic in weight and rhyme, and was the second chapter A study of the morphological level and to clarify the extent of the impact of the single building in the context and the nature of poetic compositions, And presented at the end of the chapter study of some phenomena Allahjah in his hair, and was chapter looks at the grammatical structures and some phenomena grammatical rare, either Chapter IV is a study in the significance and meanings of his words, which is known for the quality of installation and bizarre pronunciation and the scarcity of meanings, with highlight some of the uses Kalaguetrad and joint verbal and most important characteristic of his language and the large number of strange meanings already knew, and presented at the end of the search results that some Asthsaltha Job. I've made some factors combined for a red son a high profile among the people of the language, grammar, literature, what do Anmaz installation of health, style and quality, and purity of the language so it was said that he (the poet Eloquent). That language is an integrated unit characteristics appear in the proper installation and the beauty of the picture when formulated in special molds creator chooses to present his vision in the light of the self, and this is achieved by Altodev tools for linguistic differentiation between poets and writers.
Keywords: اللغة العربية -- الشعر العربي -- الضرورة الشعرية -- الباهلي، عمرو بن أحمر -- الدواوين والقصائد -- لغة الشعر -- نقد الشعر